PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA (Studi Kasus Pada Karyawan Bagian Produksi PT. PISMATEX Pekalongan) - Ricky Reydonizar; Sudharto Prawoto Hadi; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2013)
Labour productivity is a link between the output is the result of work by the time it takes to produce a product by labor. Productivity is one measure that is often used to determine the effectiveness of the organization. An organization can not flourish if their employees work productivity also increased especially with the high level of competition that exists in the business world. Compensation and work discipline has been found to increase employee productivity. Therefore both of these need to be considered by the company in order to increase productivity. PT. PISMATEX Pekalongan is one manufacturer that is engaged in the production of textiles that produce a superior product with a brand that is woven sarongs Elephant Sitting which increased the number of defective products in the production process.This study uses explanatory research approach to the 94 respondents with purposive sampling approach. Data collection techniques in this study using interview techniques, by means of questionnaires and literature study. The data obtained were analyzed qualitatively and quantitatively by using tools such as cross-table analysis, validity, reliability testing, simple linear regression, multiple linear regression and hypothesis testing with the t test and F test.Results of statistical analysis known that the compensation effect on employee productivity by 58.2%. While the results for the variable of work discipline effect on labor productivity of 49.6%. Together - the same motivation and discipline affect the productivity of 61.6%. The conclusion from this study is that there is a positive effect between compensation and work discipline on the productivity of the production employees PT.PISMATEX Pekalongan. Suggestions for increasing employee productivity for the company to increase its attention to the compensation and work discipline that will ultimately increase productivity of employees.